Ablation behaviour of coated Al2O3f/Al2O3 composites under oxyacetylene torch flame. (2nd January 2022) - Jin, Wen; Yang, Xiang; Wen, Zhang; Cheng-xin, Zhu; Yi, Wang; Jie, Cao; Yin-wei, Ma; Jian-hui, Cao
ABSTRACT: Oxide fibres have attracted considerable attention as protective layers for alumina composites. In this study, alumina (Al2 O3f /Al2 O3 ) matrix composites reinforced with continuous fibres were fabricated by a sol–gel process and were coated with Y2 O3 or ZrO2 to improve their ablation resistance. The ablation behaviour of the coated composites was analysed under the oxyacetylene torch flame test. The results suggested that the Y2 O3 and ZrO2 coatings as sacrificial barrier layers could protect the integrity of the composites. The linear ablation rate and mass ablation rate of composites with Y2 O3 coating were 0.00251 mm s −1 and 0.00143 g s −1, respectively; the linear ablation rate and mass ablation rate of composites with ZrO2 coating were 0.00142 mm s −1 and 0.00112 g s −1, respectively. After a 120 s ablation test at 2200°C, the coatings still showed a stable structure and a high protection performance.